Impact of index card match method on the knowledge and attitudes about leucorrhoea among adolescent girls - Yuanita Syaiful; Lilis Fatmawati; Siti Nur Qomariah; Mafrukahtul Firdani (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2021)
Leucorrhoea is a reproductive health problem that often appears in adolescents. Girls between the ages of 12-16 are at high risk of leucorrhoea. The Index Card Match (ICM) method is recognized as an effective preventive effort of the adolescent health education. This research aimed to discover the impact of the ICM method on the knowledge and attitudes about leucorrhoea among adolescent girls and prove the ICM method’s effectivity between the treatment and control groups. This study used a quasi-experimental design with a pre–post-test and control group. The population of this research was 40 adolescent girls. The sample included as many as 32 respondents using purposive sampling who were then divided into 2 groups: treatment and control, with each group consisting of 16 respondents. The independent variable was health education using the ICM method. The dependent variables were knowledge and attitude. The instruments used a questionnaire of knowledge and attitude, index card match, leaflet, and event activity unit. Data analysis used a paired T-test and the independent T-test with the significance set as p<0.05. The results of the paired sample T-test in the treatment group obtained the value of p = 0.000 (p <0.05), which means that after the ICM method there was significant improvement in the knowledge about leucorrhoea among the adolescent girls. The independent T test obtained p value = 0.000 (p <0.05), which indicated there was significant difference in knowledge between the treatment and control groups. The paired T test in the treatment group obtained the value of p = 0.000 (p <0.05), which means that after the ICM method there was significant change in the attitudes about leucorrhoea among the adolescent girls. The independent T test obtained the value of p = 0.000 (p <0.05), which indicated there was a significant difference in post-test attitudes between the treatment and control groups. Health education with the index card match method was one of the effective learning methods that could be accepted well by the respondents. As a result, the respondents could improve their learning about leucorrhoea.